Algerian-Soviet relations during the period of peaceful coexistence and the location of the Palestinian cause in it 1962/1989 A.D - Hamoudi Ibrir (Social Empowerment Journal, 2021)
Algerian-Soviet relations began when the flame of the Algerian revolution extended at the end of the fifties of the twentieth century, and its compass transformed from hostility and support for France’s role in Algeria under the pretext of non-interference in the interests of the “French peoples” to an explicit support for the “just and legitimate struggle that the Algerians are waging with courage.” What contributed In building a base of solid and solid cooperation between the two countries after the independence of Algeria in 1962. As Algeria turned into a gateway to the Soviet Union in the Maghreb, continent and Africa, and the Soviet Union turned into Algeria's "biggest ally" for nearly three decades, despite the importance of their relations, The manifestations of tension continued to prevail between them due to the lack of Soviet "enthusiasm" in supporting Algeria and the Arabs in the battles to restore the rights of the usurped Palestinian people against the Zionist entity between 1967 and 1973.